The Role of Educational Leadership in Implementing Religious Moderation Policies: An Analysis of Dayahs in East Aceh - Faizin Faizin; Yusaini Yusaini; Mustamar Iqbal Siregar (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
This study investigates the use of religious moderation in two traditional Islamic boarding schools (dayah), specifically Dayah Darul Muta’allimin Kruet Lintang and Dayah Asasul Islamiah Leuge in East Aceh, Indonesia. It especially examines institutional policies, educational practices, student character outcomes, and the problems encountered in advancing wasathiyah (moderate Islam). Utilizing a descriptive-analytical qualitative framework, data were gathered through comprehensive observations, semi-structured interviews with leaders and educators, and examination of institutional records. The results indicate that religious moderation is consistently internalized via three interconnected methods. The curricular approach incorporates the principles of tasamuh (tolerance), tawazun (balance), and i‘tidal (justice and moderation) in the examination of traditional Islamic writings (kitab kuning). The cultural approach prioritizes moral exemplification by teachers and dayah leaders, so encouraging moderation through quotidian practices and institutional standards. The social approach implements moderation through joint community initiatives, practical da‘wah (dakwah bil hal), and inter-dayah interactions. These strategies mutually foster the development of pupils' religious, tolerant, disciplined, and nationalistic character. However, obstacles remain, such as inconsistent student understanding, insufficient contextualized educational materials, and exposure to extremist ideologies on social media. This study highlights the strategic importance of dayah as essential institutions for fostering moderate, humanistic Islamic education and promoting Islam as rahmatan lil ‘alamin.